Kegiatan Literasi Awal Orang Tua pada Anak Usia Dini - Karima, Raisa; Kurniawati, Farida (Al-Athfal: Jurnal Pendidikan Anak, 2020)
This research was conducted to determine the initial literacy activities carried out by parents, family members, and caregivers at home. The research method used for this study is a systematic review that is implemented by capturing articles concerned in the research topic published between 2009–2019 through two electronic search engines, Science Direct and Sage Journals. Furthermore, article extractions were carried out to filter out articles that were relevant to the research question (n = 9) with five articles with mother-child participants, 1 article with caregiver-child participants, and three articles with mother or father-child participants. Data analysis in this study is done by narrative synthesis analysis. The results of this study show several activities, i.e., shared reading or book reading, grocery games, writing letters, spelling, drawing pictures, and writing spontaneously. The most popular activity is the shared reading or reading book, which has more impact on the type of book and parent involvement. Limitations and recommendations for future research are discussed in this paper.